Das penas às flautas : ornamentos e instrumentos Enawenê Nawê no ritual Yaokwa - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The report addresses the preservation of the Enawenê Nawê culture, an indigenous group that inhabits the northwest region of the State of Mato Grosso near the Juruena River with an estimated population of 1,000 individuals. This ethnic group has a huge cultural tradition based on the relationship between nature and ancestry through rituals. The Enawenê Nawê face significant challenges in their struggle to preserve their culture and territory, as the pressure of deforestation and agrarian expansion are daily threats to their way of life, since the Indigenous Land (T.I) is located on the borders of monoculture farms, logging and even invasions by prospectors. In addition, the precarious access to basic health and education services causes the ethnic group to lose its identity and craft techniques over the years. Thus, in constant collective work between the community and the researcher, it was possible to create means for the elaboration of a didactic image book in dictionary format containing the ornaments and instruments used during the Yaokwa ritual. Carrying out the maintenance of cultural heritage through Heritage Education is understanding how memory and culture are intermediaries in the development of resistance by indigenous peoples.
Keywords: Arte; Cultura; Enawenê Nawê; Yaokwa; Patrimônio; Art; Culture; Patrimony; ARTES::ARTES PLASTICAS; CIENCIAS HUMANAS::HISTORIA